Monochorionic Diamniotic Twin Pregnancy With Selective Iugr Type 2: Sonographic And Fetoscopic Findings Of Ominous Prognosis - Gil-Guevara, Enrique Damián (2016)
A pregnant woman with monochorionic twins was referred to our Centre due to discrepancy in size between the twins. She was 17 weeks pregnant when we made the diagnosis of selective IUGR type 2 and we decided to perform a fetoscopic Laser ablation of the placental anastomoses. During the fetoscopy, we identified an arterio-venous anastomosis with bidirectional flux that is completely atypical in these anastomoses, never reported before, thus representing a sign of bad prognosis for the small twin.